2020
DOI: 10.3390/cancers12082233
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Free Detection of Long Non-Coding HOTAIR RNA in Ovarian Cancer Cell Lines and Plasma Samples

Abstract: Long non-coding RNA HOX transcript antisense intergenic RNA (HOTAIR) is one of the promising biomarkers that has widely been used in determining the stages of many cancers, including ovarian cancer. In cancer diagnostics, the two key analytical challenges for detecting long non-coding RNA biomarkers are i) the low concentration levels (nM to fM range) in which they are found and ii) the analytical method where broad dynamic range is required (four to six orders of magnitude) due to the large variation in expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Advanced stage at diagnosis, poor prognosis and high incidence of resistance to therapy account for the most critical hurdles for ovarian cancer patients. Recently, our group has developed an amplification-free platform for the naked-eye observation and electrochemical quantification of long non-coding RNAs in ovarian cancer patients [16]. DNA methylation is another biomarker that plays a vital role in ovarian cancer, with several tumour suppressor genes shown to be hypermethylated [17].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced stage at diagnosis, poor prognosis and high incidence of resistance to therapy account for the most critical hurdles for ovarian cancer patients. Recently, our group has developed an amplification-free platform for the naked-eye observation and electrochemical quantification of long non-coding RNAs in ovarian cancer patients [16]. DNA methylation is another biomarker that plays a vital role in ovarian cancer, with several tumour suppressor genes shown to be hypermethylated [17].…”
Section: Introductionmentioning
confidence: 99%
“…A peptide nucleic acid (PNA) designed to specifically block the activity of HOTAIR has been successful in reducing ovarian tumor growth in vitro and in vivo, and improved survival of xenograft mice, and has been suggested as a potential new therapeutic approach for the treatment of OC [170]. The potential use of this lncRNA as a biomarker has led to the development of various methods for detection of this lncRNA from samples derived from patients with OC, primarily plasma [171,172].…”
Section: Hotairmentioning
confidence: 99%
“…This is especially true for lncRNAs encoded by a single exon, such as MALAT1 [251]. Soda et al, have recently demonstrated that HOTAIR can be detected from plasma samples using electrochemical detection, and they propose that this assay could be used in a clinical setting for the detection of various lncRNA biomarkers [172]. It is also possible to detect microproteins encoded by lncRNAs in the extracellular vesicles in human plasma samples, and these microproteins could be used as diagnostic markers [252].…”
Section: Circulating Lncrnas As Diagnostic and Prognostic Biomarkers For Ocsmentioning
confidence: 99%
“…Alternatively, microfluidic technology can address the limitations associated with conventional ISF sampling techniques. Microfluidics is an emerging science and technology that can offer significant improvements over various fields, including surface science [15], porous systems [16], nanotechnology for disease diagnosis [17], mixing [18], and separation [19,20], mechanobiology [21], cancer research [22,23], cell culture [24,25], single-cell analysis [26], drug delivery at cellular [27] and tissue levels [28], electrochemical biosensing [29], and POC sensing [30]. Furthermore, the emerging field of micro elastofluidics can provide microfluidic solutions for a flexible, conformal system attached to the skin [27].…”
Section: Introductionmentioning
confidence: 99%